Moderasi Beragama Dalam Pemikiran Syekh Yusuf Al-Makassari Dan Relevansinya Bagi Pendidikan Islam - Muhammad Irsyad Saifullah; Lathifah; Dina Bahriani Putri; Abu Mansur; Nurlaila (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2026)
Indonesia’s rich cultural diversity presents both opportunities and challenges in Islamic education, particularly in fostering religious moderation. This study aims to reconstruct the conceptual framework of religious moderation in the thought of Syekh Yusuf Al-Makassari and explore its relevance for contemporary Islamic education. Employing a library research method, the study systematically reviews primary texts by Syekh Yusuf alongside recent academic literature published between 2021 and 2025. Data were collected through document analysis and processed using qualitative content analysis techniques. The population includes classical works and scholarly articles, with purposive sampling focusing on sources with high academic credibility. Findings reveal Syekh Yusuf’s integration of tasawuf ethics, social harmony, and balanced spirituality underpinning four key principles of moderation: tawasuth, tawazun, tasamuh, and musawah. These principles provide a holistic moral framework applicable to character education and deradicalization efforts. The conclusion highlights that Syekh Yusuf’s thought offers practical and ethical foundations for inclusive educational curricula, promoting tolerant, balanced, and socially responsible Islamic learning.